Quo Vadis Penatausahaan Tanah Ulayat di Indonesia: Studi Komparasi dengan Sistem Pendaftaran Tanah Ulayat di Ethiopia - Tama, Berlian Widya; Manik, Putu Ratna Indriyani (Tunas Agraria, 2024)
Local norms and customs have an impact on the laws in Indonesia regarding the ownership of customary land by customary law communities (MHA). Even though the 1945 Constitution of the Republic of Indonesia recognizes the rights of indigenous peoples, the existing regulations lack legal certainty due to overlapping laws and regulations. The diversity of culture and relatively old society in Ethiopia make it relevant to compare regulations in Indonesia. Data collection was carried out through a library study using secondary legal data sources as the main reference base. The statutory-regulatory approach (statut approach), contextual approach (conceptual approach), and comparative approach (comparative approach) are used to examine the issue of customary land administration in Indonesia. Then the findings and data analysis will be presented in a qualitative, descriptive manner. Indonesia and Ethiopia, which have similar legal codification systems and a diversity of customs, make it easier for Indonesia to adopt Ethiopia's efforts to prosper and fulfill the interests of its MHA through continuous codification with each other in order to create legal certainty.   Hukum di Indonesia mengenai kepemilikan tanah ulayat oleh masyarakat hukum adat (MHA) dipengaruhi oleh norma dan adat istiadat setempat. Meskipun Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 mengakui hak-hak masyarakat adat, namun peraturan yang ada kurang memiliki kepastian hukum karena adanya tumpang tindih peraturan perundang-undangan. Keberagaman budaya dan masyarakat yang terhitung cukup tua di Ethiopia menjadikan relevan untuk membandingkan peraturan di Indonesia. Pengambilan data dilakukan melalui studi pustaka (library research) dengan menggunakan sumber data hukum sekunder sebagai landasan rujukan utama. Pendekatan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan komparatif (comparative approach) digunakan untuk menelaah isu penatausahaan tanah ulayat di Indonesia. Kemudian, temuan dan analisis data akan disajikan secara deskriptif kualitatif. Indonesia dan Ethiopia yang memiliki kesamaan sistem kodifikasi hukum dan keberagaman adat istiadat, memudahkan Indonesia untuk mengadopsi upaya Ethiopia dalam menyejahterakan serta memenuhi kepentingan MHAnya melalui kodifikasi yang berkesinambungan satu sama lainnya agar tercipta kepastian hukum.